Joint attention for stimuli on the hands: ownership matters - Taylor, J. E. T.; Pratt, Jay; Witt, Jessica K. (Frontiers in Psychology, 2015)
The visual system treats the space near the hands with unique, action-related priorities. For example, attention orients slowly to stimuli on the hands (Taylor & Witt, 2014). In this article, we asked whether jointly attended hands are attended in the same way. Specifically, we examined whether ownership over the hand mattered: Do we attend to our hands and the hands of others in the same way? Pairs of participants performed a spatial cueing task with stimuli that could be projected onto one partner’s hands or on a control surface. Results show delayed orienting of attention to targets appearing on the hands, but only for the owner of the hands. For an observer, others’ hands are like any other surface. This result emphasizes the importance of ownership for hand-based effects on vision, and in doing so, is inconsistent with some expectations of the joint action literature.